PENGARUH KUALITAS PROGRAM CUSTOMER RELATIONS TERHADAP TINGKAT KEPERCAYAAN PELANGGAN - Denada Lubis (Universitas Mercu Buana, 2019)
Kuningan City Mall is one of the property industry fields, namely a shopping mall that was established in 2012 in South Jakarta. Along with the development of the retail service industry, Kuningan City Mall is well aware of the importance of quality customer relations programs to increase customer trust which leads to satisfaction and profitability. In realizing customer trust requires a good or positive experience from a company. This experience can be realized through good communication in customer relations program activities, in this case Kuningan City Mall develops a